Perspective and Metamorphosis from the Renaissance to Amazonia - Capozziello, Emanuele (Aesthetica Preprint, 2025)
In this article, I aim to create a dialogue between “perspectivist” anthropology and the concept of “perspective” in aesthetics and art history. By juxtaposing the two, I will explore the emergence of an anthropological theory of representation that points toward a “reversal” of the Western perspectivist paradigm. The first part will delve into the notion of perspective as a distinctly modern and Western “scopic regime,” while the second part will examine anthropological perspectivism as a form of “reversal” of the first. This reversal will be characterized as pointing toward a “metamorphic” conception of perspective within the ethno-anthropological framework. I will argue that, in anthropological perspectivism, “having a perspective on the other” involves an openness to adopting their form, whether as a risk or an opportunity. Thus, “putting the other into perspective (as an object)” transforms into “assuming the perspective of the other (as a subject).”